Electronic structures and magnetic properties of (Cr, Fe) co-doped 3C-SiC. (4th September 2019) - Lin, Long; Yao, Linwei; Yu, Weiyang; Zhu, Linghao; Huang, Jingtao; Zhang, Zhi
Abstract: Based on density functional theory, the electronic structures and magnetic properties of 3C-SiC doped with Cr, Fe and (Cr, Fe) were studied theoretically. The results of the density of states show that Cr, Fe doped and (Cr, Fe) co-doped 3C-SiC are all half-metallic. Eight co-doped positions are calculated by using GGA and GGA+U methods, respectively. We found that the adoption of GGA+U method has better ferromagnetic coupling, and the ferromagnetism has been greatly improved. In addition, measurement of magnetic properties indicated that substituting a very light percentage of Cr and Fe for Si atoms in 3C-SiC system, the Fe atom possesses larger magnetic moments than Cr atom and (Cr, Fe) co-doped exhibits more stable ferromagnetism with a Curie temperature up to 914 K. We found that the ferromagnetism results from the strong hybridization between Cr:3 d, Fe:3 d and C:2 p states. The results show that Cr or Fe atoms substitutional doping on the Si sites in 3C-SiC could be a potential route to fabricating the diluted magnetic semiconductors.